A Novel and Rapid Isothermal Nucleic Acid Based Detection Assay of Vibrio cholerae by Polymerase Spiral Reaction (PSR) in Emergency Situations - Vahid Louhrasby; Seyed Ali Mirhosseini; Reza Golmohammadi (Tehran University of Medical Sciences, 2022)
Background: The purpose of this survey was to develop a novel and rapid isothermal nucleic acid based detection assay of Vibrio cholerae by polymerase spiral reaction (PSR) in emergency situations. Methods: The current study was conducted in Baqiyatallah University of Medical Sciences, Tehran, Iran in 2021. The conserved ctxA gene sequence of V. cholerae was used as a target of designed two pairs of primers. Amplification of nucleic acids performed under isothermal temperature of 65 oC in 55 min by using Bst DNA polymerase. PSR amplified products were real-time visualized under UV transilluminator and also on agarose gel electrophoresis. Results: Seven non- V. cholerae bacteria were negative for detection, which indicated the specificity of PSR assay was 100%. A 10- fold serial dilution of V. cholerae genomic DNA was subjected to conventional polymerase chain reaction (PCR) and real-time PCR to compare their sensitivities with PSR. The detection limit of PSR was 3 × 10-5 ng/ μL within 60 min, which 100-fold higher than that of PCR (3 × 10-3 ng/μL), but the sensitivity of real-time PCR was found as same as it. Conclusion: The PSR assay developed in this study can provide a simple, cost-effective, rapid, and precise diagnosis technique in endemic cholera outbreaks, especially in low-income with limited access provinces.